The reform of the chapter of sées (1131) reconsidered: the evidence of the episcopal acta - Allen, R (Cambridge University Press, 2016)
This paper reexamines the reform of the cathedral chapter of Sées in 1131. It does so by looking primarily, though not exclusively, at the almost 400 acta – that is, the charters and documents –issued by the bishops of the diocese in the period up to 1220. It shows that this underused material has the potential better to contextualise this key event in the ecclesiastical history of medieval France and radically to improve our understanding of its wider effects. It also looks in detail at the careers of the bishops during this period and shows that these prelates, contrary to popular belief, were often supportive not only of the reform established within their cathedral, but also of the wider Augustinian movement. It concludes by briefly considering what the example of Sées can tell us about the regularisation of cathedral chapters in the Middle Ages.